Step 1: Simplifying the numerator:
\[
0.963 \times 0.963 = 0.927369, \quad 0.963 \times 0.037 = 0.035691, \quad 0.037 \times 0.037 = 0.001369
\]
Thus, the numerator is:
\[
0.927369 - 0.035691 + 0.001369 = 0.893047
\]
Step 2: Simplifying the denominator:
\[
0.963 \times 0.963 \times 0.963 = 0.894786, \quad 0.037 \times 0.037 \times 0.037 = 0.000050653
\]
Thus, the denominator is:
\[
0.894786 + 0.000050653 = 0.894836653
\]
Step 3: Dividing the numerator by the denominator:
\[
\frac{0.893047}{0.894836653} \approx 1.000
\]
Thus, the value of the expression is \( 1 \).